2021
DOI: 10.3390/insects12010032
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Cucurbitacin B and Epigallocatechin Gallate as Biopesticides against Aphis gossypii

Abstract: Aphis gossypii (Glover) is distributed worldwide and causes substantial economic and ecological problems owing to its rapid reproduction and high pesticide resistance. Plant-derived cucurbitacin B (CucB) and epigallocatechin gallate (EGCG) are known to have insecticidal and repellent activities. However, their insecticidal activity on cotton- and cucurbit-specialized aphids (CO and CU), the two important host biotypes of A. gossypii, remains to be investigated. In the present study, we characterized, for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Obtained results indicated that synergistic effect greatly induced the relative GST and AchE activities compared to control treatment. The enhanced defenserelated enzymatic response revealed especially from the interaction treatments (synergistic interactions) with a higher proportion of % (+)-α-Pinene represents date palm dust mites response, which ultimately leads to strong physiological stress also confirmed by previous studies conducted on the host defense mechanism [54][55][56][57]. Furthermore, our results on the physiological impacts of (+)-α-Pinene and B. bassiana ARSEF 8465 conidia against date palm dust mites are consistent with those of Zibaee and Bandani [58], who reported significantly enhanced GST response among Eurygaster integriceps Puton exposed with Artemisia annua.…”
Section: Discussionsupporting
confidence: 72%
“…Obtained results indicated that synergistic effect greatly induced the relative GST and AchE activities compared to control treatment. The enhanced defenserelated enzymatic response revealed especially from the interaction treatments (synergistic interactions) with a higher proportion of % (+)-α-Pinene represents date palm dust mites response, which ultimately leads to strong physiological stress also confirmed by previous studies conducted on the host defense mechanism [54][55][56][57]. Furthermore, our results on the physiological impacts of (+)-α-Pinene and B. bassiana ARSEF 8465 conidia against date palm dust mites are consistent with those of Zibaee and Bandani [58], who reported significantly enhanced GST response among Eurygaster integriceps Puton exposed with Artemisia annua.…”
Section: Discussionsupporting
confidence: 72%
“…For instance, epicatechin was reported to be an effective antifungal defence in black poplar ( Populus nigra ) against foliar rust infection (Ullah et al, 2017); moreover, esterified gallate catechins, such as epicatechin gallate, epigallocatechin gallate and gallotannic acid, were found to induce plant defences (Goupil et al, 2020). As important components of catechins, epigallocatechin gallate, epicatechin, epigallocatechin and epicatechin gallate were verified to be effective antifungals or antifeedants against insects in vitro (Lopez et al, 2016; Zhao et al, 2021). In tea plants, most studies have mainly focused on the formation and changes of catechins under abiotic stresses to improve tea quality (Z.X.…”
Section: Introductionmentioning
confidence: 99%
“…After feeding A. gossypii on leaves treated with cucurbitacin, GST activity increased significantly (Zhao et al, 2021). Interestingly, GST showed a high level of conservation between Hap1 and Hap3.…”
Section: Detoxification Genesmentioning
confidence: 99%
“…Terpenoids and cucurbitacin are the major secondary metabolites produced by cotton and Cucurbitaceae plants, respectively (Zhao et al, 2021). We collected A. gossypii from cucumber plots that can tolerate low concentrations of cucurbitacin B (Yousaf et al, 2018).…”
Section: Detoxification Genesmentioning
confidence: 99%
See 1 more Smart Citation